Silverlight 5 in action - Brown, Pete (Manning, 2012)
A thorough revision of the bestselling Silverlight 4 in Action . This comprehensive guide teaches Silverlight from the ground up, covering all the new v. 5 features in depth. You'll also explore WCF RIA Services, MVVM, and more, with dozens of code samples you can use in Visual Studio 2010 or the free Visual Web Developer 2010 Express. About the Book This hands-on guide explores Silverlight from the ground up, covering every feature in rich, practical detail. It is readable and the coverage is comprehensive. You'll master networking, MVVM, and more, with dozens of code samples you can use in Visual Studio or the free Visual Web Developer Express. Silverlight 5 in Action teaches you how to build desktop-quality applications you can deploy on the web. Beginners will appreciate the progression from simple examples to full applications that employ good design and coding practices. Seasoned . NET developers will love how the sample code embraces and extends what they already know. What's Inside 2D and 3D graphics and animation Business application services, rules, and validation The MVVM pattern and testing 5 free appendixes (150 pages) available online A background in C# or VB.NET is helpful, but no knowledge of Silverlight or XAML is required. About the Author Pete Brown leads Microsoft 's Silverlight/ XAML Developer Community team. He's been a Silverlight MVP, an INETA speaker, and successful RIA Architect.